Isolation of Salmonella from the egg-laying producing plant - KOIDIS (Π. ΚΟΙΔΗΣ) P.; BORI (Μ. ΜΠΟΡΗ) M. (Journal of the Hellenic Veterinary Medical Society, 2018)
In the present paper, the presence of Salmonella spp. in the egg-laying hens producing plants in Thessaloniki area was studied. In total, 2.230 eggshell samples, 588 samples surfaces from floor, walls, conveyor belts, utensils and packaging areas, 168 feed samples and 68 water samples were examined. The survey showed that the rate of contamination in the eggshells was 0.29-3.29% (mean value 1.65%). The contamination rate of the surrounding area of the cages (floor, walls, conveyor belts) and the surfaces in the packaging areas were 6.81% and 7.58% respectively. The feed was contaminated at a rate of 0-6.6% (mean value 4.2%), while all the water samples were free of Salmonella spp. Eighty-six strains of Salmonella were isolated belonging to the S. enteritidis serotype (76.8%), S. bredeney (20.29%) and S. Heidelberg (2,3%). The high prevalence of S. enteritidis, in contrast to the other serotypes, isolated from the eggshells, from the area of the egg producing plants and the feed, showed that strict preventive measures should be applied for the protection of public health and the avoidance of dispersion of Salmonella in the environment.